Some Small-Scale Industries Based on Timbers of the Himalayan Region of Uttar Pradesh - Sharma, S. N.; Nath, Prem; Gupta, P. G. (Indian Forester, 1978)
Some small-scale industries based on timbers of the Himalayan region and suitable for establishment in the hill areas have been described. These are manufacture of compressed wood shuttle blocks, cotton mill pirn blocks, pencil slats, tool handles and tent mallet heads, semi-finished frames of tennis and badminton rackets, mathematical instruments etc. Approximate investments involved, machinery and inputs required and manufacturing proceses have also been briefly indicated.